Correlation study between financial and maintenance factor in facilities management of government hospitals: A study in Klang valley, Malaysia - Ibrahim, Md. Najib; Yahya, Mohamad Ridzuan (2011)

(untitled)
It is important to focus on developing facilities management (FM) aspect in the hospital in order to make sure it is in good condition and positive performance all the time. In Malaysia scenario, various obstacles have to be faced by the FM for controlling all activities related to the hospital and its system. The crucial issue is to do planned and unplanned maintenance supported by adequate budget in FM. This research explores the relationship between financial factors and maintenance factors of FM component. The financial factors are resources, allocation and expenses while the maintenance factors are quality of work, quality of safety and health, and quality of maintenance. This study will show which financial factor has strong impact on maintenance factors. They had influenced on the effectiveness of FM in hospital. This paper presents the finding of five (5) government hospitals in Klang Valley, Malaysia on FM aspect. The operational management of FM personnel, Patient (P) and Outsourcing Contractor and Consultant (OS) were interviewed for their immediate views and responses by using standard questionnaire survey. A statistical analysis based on the Pearson correlation was used to identify the correlation for each factor. As a result, the correlation coefficient (r-value) shows that there was a strong relationship between financial resources and maintenance factors. In other word, the financial resources have a positive correlation with all maintenance factors. Hence, if the maintenance management had enough financial resources, then the FM aspect will be properly managed.